Green engineering principles and application: bioremediation - Hadibarata, Tony; Voijant Tangahu, Bieby (Environmental and Toxicology Management, 2021)
The adulteration of the environment by hazardous waste, such as heavy metals, nuclear wastes, hydrocarbons, pesticides and greenhouse gases is the major serious problem which need to be reduced. Common remediation technique such as physical, chemical and biological process are being applied. Chemical process can transform and change organic contaminant of interest which is not sufficient to clean the environment, while physical technique requires additional equipment. Thus, bioremediation exist as green approach to eliminate the hazardous waste in the environment. In this review, bioremediation is comprehensively presented. Remediation process types, challenges, limitations, mechanisms, and future suggestion has been elaborated to develop bioremediation technology for future prospect.